Variability in conditioned pain modulation predicts response to NSAID treatment in patients with knee osteoarthritis. Issue 1 (December 2016) - Edwards, Robert; Dolman, Andrew; Martel, Marc.; Finan, Patrick; Lazaridou, Asimina; Cornelius, Marise; Wasan, Ajay
Abstract Background Patients with painful knee osteoarthritis (OA) demonstrate hyperalgesia and altered pain-modulatory responses. While some prior work has demonstrated cross-sectional associations between laboratory and clinical pain measures, it is unknown whether individual variability in quantitative sensory testing (QST) responses at baseline can prospectively predict analgesic treatment responses. Method Patients with knee OA (n = 35) were compared on QST responses to a demographically-matched pain-free control group (n = 39), after which patients completed a month-long treatment study of diclofenac sodium topical gel (1 %), applied up to 4 times daily. Results OA patients demonstrated reduced pain thresholds at multiple anatomic sites, as well as reduced conditioned pain modulation (CPM) and enhanced temporal summation of pain. The most pain-sensitive patients tended to report the most intense and neuropathic OA pain. Following diclofenac treatment, the knee OA cohort showed a roughly 30 % improvement in pain, regardless of the presence or absence of neuropathic symptoms. Baseline CPM scores, an index of endogenous pain-inhibitory capacity, were prospectively associated with treatment-related changes in clinical pain. Specifically, participants with higher CPM at baseline (i.e., better functioning endogenous pain-inhibitory systems) showed more reduction in pain at the end of treatment (p < .05). Conclusions These results support prior findings of amplified pain sensitivity and reduced pain-inhibition in OA patients. Moreover, the moderate to strong associations between laboratory-based measures of pain sensitivity and indices of clinical pain highlight the clinical relevance of QST in this sample. Finally, the prospective association between CPM and diclofenac response suggests that QST-based phenotyping may have utility in explaining inter-patient variability in long-term analgesic treatment outcomes. Trial registration ClinicalTrials.Gov Identifier:NCT01383954 . Registered June 22, 2011.